PENGARUH PENGGUNAAN METODE SPEED READING TERHADAP KEMAMPUAN MEMBACA CEPAT DALAM PEMBELAJARAN BAHASA INDONESIA - Khairunnisa, Khairunnisa; Syahid, Ahmad; Nurfaizah, Andi; Ardiansyah, Andi (AT TA'LIM : Jurnal Madrasah Ibtidaiyah, 2025)
This look at objectives to analyze the impact of the rate studying method on 3 middle additives of analyzing talents: analyzing pace, reading comprehension, and analyzing accuracy among fifth-grade students at SD DDI Kota Palu. A quantitative technique turned into hired using a pre-experimental one-group pretest-posttest layout. The sample consisted of all 20 college students inside the fifth grade, decided on thru overall sampling. information have been accumulated the use of a series of analyzing exams designed to measure pace, comprehension, and accuracy earlier than and after the intervention. The Shapiro-Wilk check was used to evaluate facts normality, and the Wilcoxon signed-rank check changed into implemented to decide the importance of the variations because of non-regular distribution. The consequences verified statistically sizeable enhancements across all measured variables: reading velocity multiplied from a mean of ninety phrases consistent with minute to 138 phrases according to minute, comprehension scores improved from 56 to eighty four, and reading accuracy rankings rose from 2.6 to 4.2. The Wilcoxon take a look at yielded a significance cost of 0.000 (< 0.05), indicating a tremendous difference among pretest and posttest effects. those findings advocate that the velocity analyzing approach is effective in improving elementary college students' reading performance comprehensively. The look at contributes to the developing frame of evidence supporting information-driven reading preparation strategies in primary schooling.